2020
DOI: 10.12691/jfnr-8-9-5
|View full text |Cite
|
Sign up to set email alerts
|

Family Meal Planning under COVID-19 Scarcity Constraints: A Linear Programming Approach

Abstract: The "Diet Problem" originated in the 1940s when researchers were tasked with determining the lowest-cost subsistence diet for a U.S. soldier. Originally, the task was accomplished through basic heuristics, but later the problem was solved using the simplex algorithm-the basis for modern linear programming. Enhancements to computing technology enabled further constraint consideration, including environmental and palatability constraints. In late 2019, the COVID-19 pandemic began to sweep the planet, resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…It is therefore encouraging that efficient food use behaviors started during the pandemic may be continued, as shown by intentional declarations [ 119 ]. Moreover, it was also shown that even in times of pandemic characterized by food scarcity constraints, a palatable and diversified diet can be purchased very inexpensively from supermarkets, and visits to the supermarket can also be limited to one per month to reduce dangerous exposure, given effective meal planning is put in place [ 146 ]. These findings may inform future strategies relating to meal planning and waste management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore encouraging that efficient food use behaviors started during the pandemic may be continued, as shown by intentional declarations [ 119 ]. Moreover, it was also shown that even in times of pandemic characterized by food scarcity constraints, a palatable and diversified diet can be purchased very inexpensively from supermarkets, and visits to the supermarket can also be limited to one per month to reduce dangerous exposure, given effective meal planning is put in place [ 146 ]. These findings may inform future strategies relating to meal planning and waste management.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, in the UK, ‘a newly vulnerable group who were financially stable pre-COVID emerged, making reliance on overstretched food banks and food aid charities no longer a sustainable solution to food insecurity’ [ 151 ]. On the other hand, even in times of pandemic, a healthy diet can be maintained inexpensively through infrequent visits to the supermarket [ 146 ]. Nevertheless, for low-income families, making their eating habits more sustainable would require policy responses to low income, food access, and to the high cost of healthy foods [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently Joanis ( 2020 ) has revisited the diet problem illustrating a hypothetical case of a US family in the context of some of the aforementioned challenges induced by the pandemic. In particular, he demonstrates how to feed a family effectively during a pandemic using the linear programming (LP) method, thus, minimising family food costs subject to nutritional constraints, food availability, palatability of food combinations, and meal variation.…”
Section: Relevant Literaturementioning
confidence: 99%
“…➢ Pada pengabdian pada masyarakat ini diharapkan dihasilkan video tutorial memasak, dimana pengajar akan menjelaskan bagaimana persiapan memasak, cara memasak, secara ringkas jelas. [6]. Pengajar mengajar secara online, di ruang guru, menggunakan laptop, dan peralatan bantu extended monitor, microphon smartphone, sound power.…”
Section: Pendahuluanunclassified